Chromosomal phylogeny and karyotype evolution in x=7 crucifer species (Brassicaceae) - Mandáková, Terezie; Lysak, Martin A (The Plant cell, 2008)
Karyotype evolution in species with identical chromosome number but belonging to distinct phylogenetic clades is a long-standing question of plant biology, intractable by conventional cytogenetic techniques. Here, we apply comparative chromosome painting (CCP) to reconstruct karyotype evolution in eight species with x=7 (2n=14, 28) chromosomes from six Brassicaceae tribes. CCP data allowed us to reconstruct an ancestral Proto-Calepineae Karyotype (PCK; n=7) shared by all x=7 species analyzed. The PCK has been preserved in the tribes Calepineae, Conringieae, and Noccaeeae, whereas karyotypes of Eutremeae, Isatideae, and Sisymbrieae are characterized by an additional translocation. The inferred chromosomal phylogeny provided compelling evidence for a monophyletic origin of the x=7 tribes. Moreover, chromosomal data along with previously published gene phylogenies strongly suggest the PCK to represent an ancestral karyotype of the tribe Brassiceae prior to its tribe-specific whole-genome triplication. As the PCK shares five chromosomes and conserved associations of genomic blocks with the putative Ancestral Crucifer Karyotype (n=8) of crucifer Lineage I, we propose that both karyotypes descended from a common ancestor. A tentative origin of the PCK via chromosome number reduction from n=8 to n=7 is outlined. Comparative chromosome maps of two important model species, Noccaea caerulescens and Thellungiella halophila, and complete karyotypes of two purported autotetraploid Calepineae species (2n=4x=28) were reconstructed by CCP.
Keywords: molekulární evoluce; chromozomy rostlin; karyotypizace; Chromosome Painting; Chromosomes, Plant; Translocation, Genetic; druhová specificita; translokace genetická; heterochromatin; malování chromozomů; Karyotyping; Phylogeny; fylogeneze; Heterochromatin; Brassicaceae; Species Specificity; Evolution, Molecular